Formulation of M/A-Type Ointment Dosage From Ethanol Extract of White Plumeria Leaves (Plumeria alba l.) Against Candida albicans - Dian Riana Ningsih; Zusfahair Zusfahair; Dwi Kartika; Mei Lianasari (Chemistry Department, The University of Brawijaya, 2018)
Candida albicans is one of fungi that can cause various infections. This fungal infection is known as candidiasis and some people often suffer from candidiasis. The sweaty and moisty skin is a factor that allows the growth of fungi causing skin diseases. The plants that can be used as antifungal is white plumeria leaves (Plumeria alba L.). Ethanol extract of white plumeria leaves contains alkaloid and saponin active compounds, to ease its use and to get the maximum effect, then white plumeria leaves are formulated into ointment dosage form. This research is to know the antifungal activity of extract, to formulate ointment and to know the characteristic of the extract. The research begins with determination of minimum inhibitory concentration (MIC) of extract against C. albicans, then formulation of ointment dosage. The physical properties of the ointment is tested including homogeneity test, pH, dispersive power, protection power, adhesion and hedonic and antifungal activity. The method used in determining MIC and the activity test of dosage is agar-well diffusion method. The MIC value of extract was 5 ppm with a 1.22 mm inhibition zone. Extract has a form of semisolid, white colour, distinctive odor, homogeneous, protective, pH of 5.07-5.59, dispersive power of 5,09-5,78 cm, adhesion of 1.00-2.33 seconds and antifungal activity of ointment at day 0 for concentrations of 5, 10 and 15 ppm respectively are 2.93; 5.2 and 7.87 mm and at day 15 for concentrations of 5, 10 and 15 ppm respectively are 3.68; 4.87 and 5.82 m